Local Wisdom–Based Technology Strategies for a Sustainable Blue Economy in Indonesia - Ruth Natalia Achmad; Elvando Lionel Hanas; Yerimias Manuhutu (Pattimura Proceeding, 2026)
In the global world Indonesia’s strategic position as the world’s largest archipelagic state provides significant potential for developing a sustainable blue economy. However, geographical fragmentation, technological gaps, and socio-cultural diversity require development strategies that integrate technological innovation with local wisdom. This study aims to analyze strategies for utilizing local wisdom–based technology to strengthen the sustainable blue economy in the Indonesian archipelago. This research employs a qualitative literature review method, analyzing academic articles, government reports, and international publications published between 2015 and 2025. The findings indicate that integrating digital technologies with indigenous management systems—such as sasi laut, panglima laot, and awig-awig—enhances marine resource governance efficiency while preserving ecological sustainability and social legitimacy. This study concludes that synergy between technology and local wisdom is a key foundation for inclusive, adaptive, and sustainable blue economy development in archipelagic regions.